1998
DOI: 10.1080/741942361
|View full text |Cite
|
Sign up to set email alerts
|

Unusualness and Threat as Possible Causes of "Weapon Focus"

Abstract: In two experiments exploring possible causes of the "weapon focus" effect, undergraduates viewed videotapes depicting interactions in business establishments. The target character was either empty-handed or held different objects that varied in both threat and unusualness. Witnesses attempted to describe the target's features and clothing, identify the object held by him (if any), and identify him in a photo line-up. The accuracy of witnesses' descriptions was affected by unusualness but not threat. Identifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
100
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(113 citation statements)
references
References 14 publications
9
100
4
Order By: Relevance
“…Specifically, arming an observer may reduce the unusualness of weapons in a scene. People tend to look more at objects when they are unexpected in a scene (Loftus & Mackworth, 1978), and because weapons are not generally expected in everyday situations, their unexpected presence could account for a weapon focus effect (Pickel, 1998). To address this issue, we compared the dwell times in the first half of the experiment with dwell times in the second half of the experiment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, arming an observer may reduce the unusualness of weapons in a scene. People tend to look more at objects when they are unexpected in a scene (Loftus & Mackworth, 1978), and because weapons are not generally expected in everyday situations, their unexpected presence could account for a weapon focus effect (Pickel, 1998). To address this issue, we compared the dwell times in the first half of the experiment with dwell times in the second half of the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Any weapon is inherently significant in a scene because of the potential danger, but alternative explanations have suggested that the weapon focus effect can also be explained by unusualness (e.g., Pickel, 1998Pickel, , 1999. These two possibilities are not mutually exclusive, and both could lead to an increase in attention paid to weapons, relative to other objects.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, weapon focus has been observed in the absence of emotion, indicating the importance of the weapon's potency as an attention magnet (Kramer, Buckhout, & Eugenio, 1990;Maass & Köhnken, 1989). In addition, several studies speak directly to the claim that weapon focus is observed precisely because the weapon is a surprising and novel stimulus (Mitchell, Livosky, & Mather, 1998;Pickel, 1998Pickel, , 1999. Other studies, however, suggest that the strength of the weapon-focus effect increases as arousal increases, indicating that arousal also plays a role (e.g., Peters, 1988).…”
mentioning
confidence: 99%
“…The presence of a weapon may, therefore, be contextually inappropriate. For example, Pickel (1998) manipulated unusualness and threat but found that only unusualness impacted memory (see also Pickel, Ross, & Truelove, 2006). This finding suggests that it may be unusualness, rather than threat, that captures our attention.…”
mentioning
confidence: 99%